Dolphin Ecotourism: Applying the "Tri Mandala" Framework to Balance Tourism, Conservation, and Culture in North Bali - I Putu Ananda Citra; Abd Razak Zakaria; Made Dwipayana; I Gede Putu Eka Suryana (Jurnal Kajian Bali (Journal of Bali Studies), 2025)
Dolphin ecotourism in Lovina, North Bali, poses ecological risks due to uncontrolled human interactions and limited community awareness. To address these challenges, a culturally grounded yet environmentally conscious framework is essential. This study introduces the Tri Mandala concept, rooted in the Tri Hita Karana philosophy, which emphasizes harmony between humans, nature, and spirituality. The research employs qualitative analysis, including stakeholder interviews and field observations, to assess cultural and environmental synergies. The Tri Mandala organizes ecotourism activities into three spatial zones:  utama (sacred), madya (intermediate), and nista mandala (profane), each serving distinct functions. A minimum dolphin observation distance of 50 meters is recommended to reduce ecological disruption. This zoning model promotes balanced interactions among stakeholders, fostering sustainability and cultural integrity. Future adaptations should incorporate ecological, spatial metrics and cross-cultural testing to enhance relevance. This approach highlights the need for context-sensitive methodologies in ecotourism planning, balancing local values with scalable conservation strategies.